2020
DOI: 10.1371/journal.pone.0241705
|View full text |Cite
|
Sign up to set email alerts
|

Ethno-veterinary uses of Poaceae in Punjab, Pakistan

Abstract: Plant species of the Poaceae family are not only used as fodder and forage but also contribute substantially to the treatment of various health disorders, particularly in livestock. Consequently, the present study was aimed to document the therapeutic uses of Poaceae practiced by the inhabitants of the Punjab Province for the treatment of various veterinary health disorders. Semi structured interviews, group discussion and field walks were conducted to collect the data. Quantitative indices including cultural … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(44 citation statements)
references
References 92 publications
7
29
0
Order By: Relevance
“…families groups with high species richness most likely contain a great diversity of morphological and chemical properties [ 35 ] (flavonoids, alkaloids, saponins, terpenes, coumarins, organosulfur compounds, glycosides, steroids, tannin, mucus, lignans, anthraquinones, aromatic constituents, phenolic lipids, carotenoids, steroids, and), from which potential multiple uses can be derived. These results are in general agreement with previous ethnobotanical inventories which indicated that the most prominent families were Asteraceae Lamiaceae, Fabaceae Poaceae, Apiaceae, and Solanaceae [ 2 , 11 , 12 , 36 40 ].…”
Section: Discussionsupporting
confidence: 92%
“…families groups with high species richness most likely contain a great diversity of morphological and chemical properties [ 35 ] (flavonoids, alkaloids, saponins, terpenes, coumarins, organosulfur compounds, glycosides, steroids, tannin, mucus, lignans, anthraquinones, aromatic constituents, phenolic lipids, carotenoids, steroids, and), from which potential multiple uses can be derived. These results are in general agreement with previous ethnobotanical inventories which indicated that the most prominent families were Asteraceae Lamiaceae, Fabaceae Poaceae, Apiaceae, and Solanaceae [ 2 , 11 , 12 , 36 40 ].…”
Section: Discussionsupporting
confidence: 92%
“…The people of Jhelum have a diverse culture with distinct modes of life, traditions, and beliefs [ 56 ]. The ethnic groups of the area show a strong connection to wild plants which often have cultural and medicinal significance [ 57 ].…”
Section: Methodsmentioning
confidence: 99%
“…The people of Jhelum have a diverse culture with distinct modes of life, traditions, and beliefs [56]. The ethnic groups of the area show a strong connection to wild plants which often have cultural and medicinal significance [57]. The study was conducted in 27 remote villages ( Figure 2), all of which contained rivers, mountains, forests, salt mines, and valleys.…”
Section: Study Areamentioning
confidence: 99%
“…These findings also provide baseline information by identifying the effective herbal remedies for livestock health which can be utilized by veterinarians and pharmacologists for the development of new therapies as well as isolation of bioactive compounds [45,[59][60][61][62][63][64][65][66][67][68][69][70]. The results also serve as a conservationist's proxy and provide an insightful scientific information for the conservation management of overexploited plant species of the region [45,60,70,71].…”
Section: Plos Onementioning
confidence: 99%